Secure Real-time Data Transmission for Drone Delivery Services using Forward Prediction Scheduling SCTP - Febby Ronaldo; Amang Sudarsono; Dadet Pramadihanto (EMITTER International Journal of Engineering Technology, 2022)
Drone technology is considered the most effective solution for the improvement of various industrial fields. As a delivery service, drones need a secure communication system that is also able to manage all of the information data in real-time. However, because the data transmission process occurs in a wireless network, data will be sent over a channel that is more unstable and vulnerable to attack. Thus, this research, purposes a Forward Prediction Scheduling-based Stream Control Transmission Protocol (FPS-SCTP) scheme that is implemented on drone data transmission system. This scheme supports piggybacking, multi-streaming, and Late Messages Filter (LMF) which will improve the real-time transmission process in IEEE 802.11 wireless network. Meanwhile, on the cybersecurity aspect, this scheme provides the embedded option feature to enable the encryption mechanism using AES and the digital signatures mechanism using ECDSA. The results show that the FPS-SCTP scheme has better network performance than the default SCTP, and provides full security services with low computation time. This research contributes to providing a communication protocol scheme that is suitable for use on the internet of drones’ environment, both in real-time and reliable security levels.